2011
DOI: 10.1016/j.cellimm.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a poly (lactide co-glycolide) encapsulated plasmid DNA expressing antigenic regions of HPV 16 and 18 results in an increase in the precursor frequency of T cells that respond to epitopes from HPV 16, 18, 6 and 11

Abstract: A phase II trial was conducted in subjects with human papillomavirus (HPV) associated high-grade cervical dysplasia testing the safety and efficacy of a microparticle encapsulated pDNA vaccine. Amolimogene expresses T cell epitopes from E6 and E7 proteins of HPV types 16 and 18. An analysis was performed on a subset of HLA-A2+ subjects to test whether CD8+ T cells specific to HPV 16, 18, 6 and 11 were increased in response to amolimogene immunization. Of the 21 subjects receiving amolimogene, 11 had elevated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Some of the peptides predicted in the study were already reported as CTL epitopes. HPV 16 peptides E1-LLQQYCLYL254-262 [34], E5-FLLCFCVLL15-23, VLLCVCLLI21-29 [35], E6-KLPQLCTEL18-26 [36,37] and E7-TLHEYMLDL7-15 [38] are known CTL epitopes. E7-LLMGTLGIV82-90 was known to induce the cellular response in HLA A2.1 rabbit model [39] and reduced tumor burden in aged mice [40].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the peptides predicted in the study were already reported as CTL epitopes. HPV 16 peptides E1-LLQQYCLYL254-262 [34], E5-FLLCFCVLL15-23, VLLCVCLLI21-29 [35], E6-KLPQLCTEL18-26 [36,37] and E7-TLHEYMLDL7-15 [38] are known CTL epitopes. E7-LLMGTLGIV82-90 was known to induce the cellular response in HLA A2.1 rabbit model [39] and reduced tumor burden in aged mice [40].…”
Section: Discussionmentioning
confidence: 99%
“…57 One of the rare nucleic acid vaccine therapies to a Phase II/III study incudes ZYC101a, an HPV-16 E7 HLA-A2 restricted peptide, which also encodes segments of HPV-16 and HPV-18 E6 and E7 viral proteins. 60,61 In a Phase II study of 21 patients receiving the vaccine, 11 had elevated CD8 þ T-cell responses to HPV-16 and/or HPV-18 peptides, and 7 of these also had increases to corresponding HPV-6 and/or HPV-11 peptides. In addition, T cells primed and expanded in vitro with an HPV-18 peptide had cross-reactivity to the corresponding HPV-11 peptide.…”
Section: Nucleic Acid-based Vaccinesmentioning
confidence: 99%
“…Another DNA preparation (Amolimogene) contains an encapsulated plasmid encoding some proteins of HPV. In a small group of patients with HPV-associated high-grade CIN, no correlation between cellular immunity and clinical response was reported [110]. Another DNA preparation (Sig-E7(detox)-HSP70) encoding a fusion protein between HPV E7 protein and heat shock protein 70 was tried in a small group of patients with HPV-induced CIN 2/3.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%